Peran Teknologi Pembelajaran pada Desain Pembelajaran - Rajiman Andrianus Sirait; Ester Yunita Dewi (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
In the digital era, technology plays an important role in designing learning that is more interactive, personalised and adaptive. This research examines the role of learning technology in learning design through a qualitative approach based on a literature review. The use of technology, such as Learning Management Systems (LMS), virtual reality (VR), and artificial intelligence (AI), shows potential to increase student engagement as well as provide a more flexible learning experience. Blended learning approaches are also proven to increase engagement and provide flexibility in the learning process. In addition, technology supports competency-based learning that enables real-time evaluation of student progress through learning analytics. However, there are challenges in implementing technology, such as the digital divide, teacher readiness, and infrastructure limitations. Therefore, the successful integration of technology in learning design requires support from educational institutions and policies to provide adequate training for teachers and appropriate technology infrastructure. This study concludes that technology integration in learning design provides significant benefits in improving learning quality, but still requires a systematic and adaptive approach.